Web-Age Information Management WAIM 2016 International Workshops, MWDA, SDMMW, and SemiBDMA, Nanchang, China, June 3-5, 2016, Revised Selected Papers - Song, Shaoxu; Tong, Yongxin (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the refereed proceedings of 3 workshops of the 17th International Conference on Web-Age Information Management, WAIM 2016, held in Nanchang, China, in June 2016. The three workshops were as follows: • The International Workshop on Spatiotemporal Data Management and Mining for the Web (SDMMW 2016) • The International Workshop on Semi-structured Big Data Management and Applications (SemiBDMA 2016). • The International Workshop on Mobile Web Data Analytics (MWDA2016).